Ocean waves across the Arctic: Attenuation due to dissipation dominates over scattering for periods longer than 19 s. Issue 11 (6th June 2016) - Ardhuin, Fabrice; Sutherland, Peter; Doble, Martin; Wadhams, Peter
Abstract: The poorly understood attenuation of surface waves in sea ice is generally attributed to the combination of scattering and dissipation. Scattering and dissipation have very different effects on the directional and temporal distribution of wave energy, making it possible to better understand their relative importance by analysis of swell directional spreading and arrival times. Here we compare results of a spectral wave model—using adjustable scattering and dissipation attenuation formulations—with wave measurements far inside the ice pack. In this case, scattering plays a negligible role in the attenuation of long swells. Specifically, scattering‐dominated attenuation would produce directional wave spectra much broader than the ones recorded, and swell events arriving later and lasting much longer than observed. Details of the dissipation process remain uncertain. Average dissipation rates are consistent with creep effects but are 12 times those expected for a laminar boundary layer under a smooth solid ice plate. Key Points: Directions of tilt in the pack ice shows narrow long‐period swell beams that are not compatible with a strong scattering Swell attenuation rates inferred from model‐data comparisons are 12 times larger than under‐ice viscous friction Dissipation rates are compatible with secondary creep effects